Dismissing an employee (Boston, Mass., 2007)
While no one likes to be the bearer of bad news, managers are sometimes faced with the difficult task of having to dismiss an employee. In this book, you'll learn how to effectively manage a dismissal--including making key decisions before, during, and after the critical event. Handled skillfully, dismissing an employee can set your team--and your company--on a positive new path.
Keywords: Employees,Công nhân; Dismissal of,Law and legislation,Sa thải,Luật va pháp luật